2021
DOI: 10.3390/ijerph181910405
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Integration of Technology-Based Interventions in the Care Pathway for People with Dementia: A Cross-National Study

Abstract: Background: The integration of technology-based interventions into health and care provision in our aging society is still a challenge especially in the care pathway for people with dementia. Objective: The study aims to: (1) identify which socio-demographic characteristics are independently associated with the use of the embodied conversational agent among subjects with dementia, (2) uncover patient cluster profiles based on these characteristics, and (3) discuss technology-based interventions challenges. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Among the studies that reported a study design, mixed method studies (8/36, 22%) [ 10 , 28 , 39 - 44 ] and pilot studies (8/36, 22%) [ 31 , 34 , 38 , 45 - 48 ] were the most commonly used study designs, followed by qualitative studies (6/36, 17%) [ 11 , 26 , 35 , 49 - 51 ], randomized controlled trials (5/36, 14%) [ 32 , 37 , 52 - 54 ], ongoing trials (4/36, 11%) [ 33 , 55 - 57 ], quasiexperimental designs (2/36, 6%) [ 30 ], longitudinal study (1/36, 3%) [ 29 ], single-group nonrandomized trial (1/36, 3%) [ 36 ], and pre- and posttest design (1/36, 3%) [ 27 ]. Of the 36 studies, 30 (83%) were conducted on patients (15/36, 42%) [ 10 , 26 , 32 , 34 - 37 , 40 , 42 , 47 , 52 , 54 - 57 ] or healthy individuals (15/36, 42%) [ 11 , 27 , 29 - 31 , 44 - 46 , 48 - 51 , 53 ] and 6 (17%) [ 28 , 33 , 38 , 39 , 41 , 43 ] on stakeholders such as homecare providers or experts. The mean age of the target population across studies was >40 years, except for 19% (7/36) of the studies [ 30 , 33 , 35 , 47 , 53 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the studies that reported a study design, mixed method studies (8/36, 22%) [ 10 , 28 , 39 - 44 ] and pilot studies (8/36, 22%) [ 31 , 34 , 38 , 45 - 48 ] were the most commonly used study designs, followed by qualitative studies (6/36, 17%) [ 11 , 26 , 35 , 49 - 51 ], randomized controlled trials (5/36, 14%) [ 32 , 37 , 52 - 54 ], ongoing trials (4/36, 11%) [ 33 , 55 - 57 ], quasiexperimental designs (2/36, 6%) [ 30 ], longitudinal study (1/36, 3%) [ 29 ], single-group nonrandomized trial (1/36, 3%) [ 36 ], and pre- and posttest design (1/36, 3%) [ 27 ]. Of the 36 studies, 30 (83%) were conducted on patients (15/36, 42%) [ 10 , 26 , 32 , 34 - 37 , 40 , 42 , 47 , 52 , 54 - 57 ] or healthy individuals (15/36, 42%) [ 11 , 27 , 29 - 31 , 44 - 46 , 48 - 51 , 53 ] and 6 (17%) [ 28 , 33 , 38 , 39 , 41 , 43 ] on stakeholders such as homecare providers or experts. The mean age of the target population across studies was >40 years, except for 19% (7/36) of the studies [ 30 , 33 , 35 , 47 , 53 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 36 studies, 8 (22%) addressed atrial fibrillation [ 34 , 52 , 55 , 56 ] and type 2 diabetes [ 10 , 26 , 37 , 39 ]. Other conditions included dementia (2/36, 6%) [ 41 , 42 ], obesity (1/36, 3%) [ 32 ], Parkinson disease (1/36, 3%) [ 36 ], sleep apnea syndrome (1/36, 3%) [ 38 ], spinal cord injury (1/36, 3%) [ 35 ], and chronic pain (3/36, 8%) [ 47 , 54 , 57 ]. One study focused on 2 diseases [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Undertaking research in dementia and other neurological degenerative diseases is complex and poses several challenges [ 98 , 99 ]. To the best of our knowledge, no other study has empirically assessed the impact of actual use behavior of healthcare wearable devices on the quality of life of PWDs in the context of developing countries using extended UTAUT and SF-36 instruments, thus making the insights from this study very useful in guiding future research in this area.…”
Section: Discussionmentioning
confidence: 99%